Urban water crisis and the promise of infrastructure: a case study of Shimla, India - Sarkar, Soma (Frontiers in Water, 2023)
Urban water configurations evolve through synergetic relationships that are non-linear, spatially variable, and temporally contingent. As urban developments grow in complexity, dense water flow networks intensify within the urban landscape and pose a major challenge in urban water governance. At this junction, the paper takes up the specific case study of the water crisis in Shimla, a city situated in the western Himalayas which was once the summer capital of British India. Shimla has witnessed two significant episodes of a severe water crisis in 2016 and 2018 respectively. While the mainstream discourses identified erratic rainfall due to climate change, urban growth, and tourism as the prime causes, the crisis was not marked by absolute scarcity. Multitude configurations of infrastructure politics, distribution, and access produced the scarcity which differentially impacted the people in the city and continues to do so. Marginalized social groups (class, caste, gender, and religion) and people living on the periphery such as the slum dwellers, daily wage laborers, and informal sector workers with inadequate economic and social safety nets seem to have been missing from the discourse. In addition, the crisis events in Shimla have led to institutional changes in the governance of water by establishing a parastatal body for a water utility in the city and the proposal of mega water infrastructure projects for the bulk supply of water from the Sutlej River. Deriving from a situated urban political ecology approach, this study presents an in-depth empirical understanding of the complex urban waterscape of Shimla city where the tourism industry is a major stakeholder, and a critical analysis of the emerging ‘new’ politics of water which is also a politics of infrastructure in Shimla’s post-crisis phase. Locating the Shimla case study within the broader planetary geography, the paper argues that the water crisis as a context is dialectical. While several hydraulic projects are implemented and there is the financialization of nature, the inherent fissures of inequality within the city that causes differential access to water remains.